NiCo(OH)2/NiCo2O4 as a Heterogeneous Catalyst for the Electrooxidation of 5-Hydroxymethylfurfural - Wen Li; Di Yin; Wanxin Liu; Yi Li; Yijin Wu (Inorganics)
The electrochemical oxidation of biomass-derived 5-hydroxymethylfurfural (HMF) coupled with water electrolysis for green hydrogen production is a promising strategy to address energy crises and environmental pollution. Despite the suitable adsorption energy for HMF due to their partially filled d-band electronic structures, Ni- or Co-based oxides/hydroxides still face challenges in insufficient activity and stability. In this study, a porous heterogeneous nickel cobalt oxide/hydroxide growth on nickel foam (NF), which is defined as NF@NiCo-H/O, was developed via immersion in concentrated alkali solution. Compared with the single-component NiCo oxides, the NF@NiCo-H/O catalyst exhibits a lower application potential of only 1.317 V, 1.395 V, and 1.443 V to achieve current densities of 20, 50, and 100 mA cm−2, respectively, in an alkaline solution containing HMF. Additionally, it demonstrates rapid reaction kinetics with a Tafel slope of 27.6 mV dec−1 and excellent cycling stability. Importantly, the presence of more high-valent Ni3+-O species on the catalyst surface contributes to its exceptional selectivity for 2,5-furandicarboxylic acid (86.7%), Faradaic efficiency (93.1%), and conversion rate (94.4%). This catalyst provides some theoretical guidance for the development of biomass electrooxidation catalysts for sustainable energy and chemical production.